Design of high-precision displacement safety monitoring and three-dimensional spatial alarm system for Beidou based on intelligent algorithms - Yuqing Cao; Weiwei Lian; Jinbiao Yang; Chunxi Zhang; Xingzhi Chang (Measurement: Sensors, 2024)
The purpose of this study is to design a system that can monitor the displacement changes of engineering structures in real time and provide timely alarms when abnormal displacement is detected, in order to provide efficient safety monitoring and early warning functions and reduce the safety risks of engineering structures. The study adopted a combination of intelligent algorithms and the Global Satellite Navigation System (Beidou). By installing high-precision displacement sensors, monitor the displacement changes of the engineering structure. Then, intelligent algorithms are used to analyze and process the data collected by the sensors in real time, in order to extract the characteristics of displacement changes. At the same time, combined with the positioning data of the BeiDou navigation system, high-precision displacement monitoring is achieved. When the monitoring results exceed the set threshold, the system will automatically trigger an alarm mechanism to promptly notify relevant personnel for processing. Through experiments and comparative analysis, the Beidou high-precision displacement safety monitoring and 3D spatial alarm system based on intelligent algorithms designed in this study can effectively monitor and alarm displacement changes. The system has the characteristics of high accuracy, real-time performance, and reliability, which can timely detect displacement anomalies and provide reliable safety monitoring and warning functions.